Direct supervision, technical competence, and work quality in school asset administration - Emanisar, Velnika; Gustitianti, Nurhizrah; Rusdinal, Rusdinal; Syahril, Syahril (Indonesian Research Journal in Education |IRJE|, 2026)
Effective school asset management depends on both organizational support and employee competence. This study examines the contribution of supervisory supervision and technical competence to the work quality of assistant property administrators in senior high schools, vocational high schools, and special schools in West Sumatra Province. A quantitative correlational design was employed involving 194 assistant property administrators selected through stratified proportional random sampling. Data were collected using a structured questionnaire and analyzed through descriptive statistics, correlation analysis, and multiple regression. The findings indicate that supervisory supervision accounts for 13.4% of work quality, while technical competence accounts for 34.7%. Simultaneously, both variables explain 40.3% of the variance in work quality, with technical competence emerging as the stronger predictor. The results suggest that improving administrative performance requires not only effective supervision by school leaders but also continuous professional development to strengthen technical capabilities. The study contributes to educational management literature by highlighting the importance of integrating supervisory practices and competency development to improve accountability and effectiveness in school asset administration.